MACROECONOMIC STABILITY OF CENTRAL AND EASTERN EUROPEAN COUNTRIES - Arnold WEISZENBACHER (EURINT, 2014)
In the context of the recent financial crisis, the macroeconomic stability of most countries has been cast to shadow. The damage to the economy caused by high inflation, volatile exchange rates, increasing amount of debts and the unstable financial markets has heavily left its toll on the global market and has led to massive unemployment and increasing poverty. This paper aims to follow the eight new Central and Eastern European countries that joined the European Union in 2004, as well as Romania and Bulgaria, who followed suit in 2007, in what concerns their economical performance, following adhesion to the EU while also comparing the periods before and after the economical crisis. They were chosen as a topic of research for the severity with which the crisis affected them and the high degree of reform implementation in the aftermath. It also plans to highlight the effect of the new reforms and the growth potential when compared to the rest of the European Union. The price inflation, real GDP growth, the levels of (un)employment, fiscal policy and stability of exchange rates will provide a clear image of how this cluster of developing countries fare nowadays against the rest of the EU countries.